Sposoby wskazywania osób w dokumentacji Towarzystwa Opieki Obywatelskiej nad Internatem dla Kandydatek Seminarium Nauczycielskiego Żeńskiego we Lwowie = The means of people`s indication in the documents of Towarzystwo Opieki Obywatelskiej nad Internatem dla Kandydatek Seminarium Nauczycielskiego Żeńskiego we Lwowie / The Society for the Civic Care of the Boarding School for Candidates of the Female Teachers` Seminary in Lviv - Wojciechowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents linguistic habits on how to address the person that have been preserved in the documents of Towarzystwo Opieki Obywatelskiej nad Internatem dla Kandydatek Seminarium Nauczycielskiego Żeńskiego we Lwowie / The Society for the Civic Care of the Boarding School for Candidates of the Female Teachers` Seminary in Lviv (1892-1907). The analysis proves that the choice of indicators is determined by: people`s features (i.e. the person`s rank, the social status of the minute taker), the formality level of the communicative situation and the genre`s requirements.
Keywords: protokół; etykieta językowa; tytulatura; 19 w.; protocol; language etiquette; titles; 19th century